Electricity Costs and the Maine Economy: Review and Prospects - Colgan, Charles (Maine Policy Review, 1994)
Rising electricity costs over the past several years have set off alarm bells about the possible effects on economic growth in Maine. Efforts to at least reduce the rate of growth of electricity prices have led to charges and countercharges between the state’s largest utility and many of the non-utility generators (NUG’s), and resulted in major battles in the recent session of the Maine Legislature. In all of the discussion, however, there has been little information about two key questions: How high are Maine’s electricity costs relative to other areas, and how sensitive is the Maine economy to changes in electricity costs? This article offers some answers to these questions based on the most recent data available on comparative costs and on an analysis of the Maine economy using a computer simulation.